(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article examines the ecological characteristics and significance of the Indian sparrow (Passer indicus) in the lower reaches of the Zeravshan River. Data on distribution, abundance, seasonal dynamics, nutrition, the species’ role in nature and agriculture, and determining factors are analyzed. The study was conducted from 2020 to 2025 in the Bukhara, Navoi, and Kashkadarya regions of Uzbekistan. The species’ specific features are attributed to changes in habitat, life cycle, environmental conditions, and trophic relationships.